(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
Leaving Emergency Departments (ED) early is an important failure of these structures, constituting a risk for the health of the people who renounce the benefits of such healthcare, and a cost to the countries that finance healthcare service for their citizens. In order to implement actions to reduce the extent of this failure, an understanding of the characteristics of patients who leave EDs early is needed. This research scrutinizes the determinants of early ED departure in the hospitals of the region of Campania, Italy, where around a tenth of the Italian population lives. We adopt a quantitative framework, utilizing a novel robust dataset of about 1,000,000 observations, employing both Probit and Logit estimators. Our analysis reveals that factors including being a woman, having Italian citizenship, arriving by ambulance, severity of condition, and reporting a trauma, are associated with decreased probability of premature ED departure, while residing in high-income municipalities and being under 65 correlate with an increased likelihood of early leaving. The value of this information for policymakers and healthcare providers is discussed.